Farm subsidies and global agricultural productivity - Mamun, Abdullah (International Food Policy Research Institute, 2024)
The agriculture sector receives substantial fiscal subsidies in various forms, including through programs that are linked to production and others that are decoupled. As the sector has reached the technology frontier in production over the last three decades or so, particularly in high- and middle-income countries, it is intriguing to investigate the impact of subsidies on productivity at aggregate level. This study examines the impact of subsidies on productivity growth in agriculture globally using a long time series on the nominal rate of assistance for 42 countries that covers over 80 percent of agricultural production. The econometric results show heterogenous effects from various subsidy instruments depending on the choice of productivity measure. Regression results suggest a strong positive effect of input subsidies on both output growth and labor productivity. A positive but relatively small impact of output subsidies is found on output growth only. Subsidies that are mostly decoupled reveal no significant impact on any of the productivity measures.